Способ разделения изотопов бора - Волк В. И. Владимир Иванович; Семенов А. А. Александр Александрович; Шугрина Н. В. Наталья Владимировна; Гаврилов П. М. Петр Михайлович; Евстафьев А. А. Алексей Алексеевич; Короткевич В. М. Владимир Михайлович
опубл. 10.12.07